Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/dneu.22157
|View full text |Cite
|
Sign up to set email alerts
|

Second messenger networks for accurate growth cone guidance

Abstract: Growth cones are able to navigate over long distances to find their appropriate target by following guidance cues that are often presented to them in the form of an extracellular gradient. These external cues are converted into gradients of specific signaling molecules inside growth cones, while at the same time these internal signals are amplified. The amplified instruction is then used to generate asymmetric changes in the growth cone turning machinery so that one side of the growth cone migrates at a rate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 120 publications
0
13
0
Order By: Relevance
“…The mechanisms by which physiological levels of ROS support neurite outgrowth and axon specification appear to involve release of calcium from intracellular stores, a potent second messenger regulating cytoskeletal organisation and dynamics (reviewed in ). Short respiratory bursts of NADPH oxidase‐generated ROS promote calcium release by redox modification of ryanodine (RyRs) and inositol‐3‐phosphate receptors (IP3Rs).…”
Section: Regulation Of Ros In the Nervous System The Case For The Dementioning
confidence: 99%
“…The mechanisms by which physiological levels of ROS support neurite outgrowth and axon specification appear to involve release of calcium from intracellular stores, a potent second messenger regulating cytoskeletal organisation and dynamics (reviewed in ). Short respiratory bursts of NADPH oxidase‐generated ROS promote calcium release by redox modification of ryanodine (RyRs) and inositol‐3‐phosphate receptors (IP3Rs).…”
Section: Regulation Of Ros In the Nervous System The Case For The Dementioning
confidence: 99%
“…; Tojima ; Dudanova & Klein ; Sutherland et al . ; Akiyama & Kamiguchi ). For example, an extracellular concentration gradient of a guidance cue evokes asymmetric Ca 2+ elevations across the inside of the growth cone, with higher Ca 2+ concentrations on the side facing the cue (Henley & Poo ; Henley et al .…”
Section: Introductionmentioning
confidence: 99%
“…The growth cone senses a variety of surrounding extracellular molecules such as trophic factors, guidance cues, and extracellular matrix (ECM) components (Tessier-Lavigne & Goodman 1996;O'Donnell et al 2009). These multiple extracellular signals are translated and integrated into intracellular second messenger networks to direct growth cone behaviors (Gomez & Zheng 2006;Tojima et al 2011;Tojima 2012;Dudanova & Klein 2013;Sutherland et al 2014;Akiyama & Kamiguchi 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In all cases, however, the mechanism of calcium signaling has not been fully understood. In animal systems, some calcium channels have been identified that could mediate calcium fluxes (Akiyama and Kamiguchi, 2015). However, little is known about the Ca 2+ transporters that mediate Ca 2+ fluxes in plant cells.…”
mentioning
confidence: 99%